2021
DOI: 10.1177/23197145211062975
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Psychological Well-being and Subjective Happiness in the New Normal: An Exploration

Abstract: The pandemic has brought in unprecedented changes in societies across the globe. It has altered the equilibrium and forced individuals to move out of their comfort zone, leading to disturbance in psychological well-being in the new normal (Kuster, 2021). This empirical study examines the effect of psychological well-being (PWB) on subjective happiness (SH) of students of higher educational institutions (HEIs) during the global pandemic. Total of 290 students of HEIs were administered with the PWB questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
3
3
0
Order By: Relevance
“…Karadeniz and Zabcı (2020) further add nuance by illustrating that elementary teachers experience significantly higher stress levels than high school teachers, whilst preschool educators manifest markedly elevated well-being levels. All these studies, along with some other existing studies (Warrier et al, 2021;Zakaria et al, 2021), corroborate our findings. However, a study conducted by Onuray Eğilmez (2022) found that teachers scored below average in terms of PWB.…”
Section: Discussion and Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Karadeniz and Zabcı (2020) further add nuance by illustrating that elementary teachers experience significantly higher stress levels than high school teachers, whilst preschool educators manifest markedly elevated well-being levels. All these studies, along with some other existing studies (Warrier et al, 2021;Zakaria et al, 2021), corroborate our findings. However, a study conducted by Onuray Eğilmez (2022) found that teachers scored below average in terms of PWB.…”
Section: Discussion and Resultssupporting
confidence: 93%
“…This result aligns with studies that indicate no variation in teachers' PWB based on gender (Arslan & Tura, 2022;Yakut & Yakut, 2018). Also, many more studies confirming the conclusion that the gender variable does not affect the PWB of teachers Singh & Sharma, 2023;Onuray Eğilmez, 2022;Warrier, 2021). However, there are alternative studies asserting that the gender factor does influence teachers' PWB (Cenkseven & Akbaş, 2007;Doğan & Aslan, 2022).…”
Section: Discussion and Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, there is scientific evidence that subjective happiness may influence the quality of life during the pandemic [12]. The concept of subjective happiness (SH) is understood as a broader term for a person's well-being, which is an indicator of how happy or unhappy one feels, not only as a personal assessment, but also in comparison with others [13,14].…”
Section: Of 14mentioning
confidence: 99%
“…The levels of SH among students were influenced by their perceptions of the educational environment [ 28 ], and those with social networks reported greater SH [ 25 ]. Students during COVID-19 experienced greater SH [ 29 ]. The relationship between SC, LS and SH among university students during COVID-19 is limited.…”
Section: Introductionmentioning
confidence: 99%